See Inside the Ancient World - Jones, Rob Lloyd; Illustrated by Ablett, Barry (Saffron Hill Usborne Publishing, 2012)
A fascinating flap book packed with interesting information about the Ancient World, from the dawn of civilization in Ancient Egypt, to the rise of the great Mayan culture in Central America. Look inside an Egyptian temple, open the doors of ancient Chinese houses, and find out what goes on behind the walls of a Roman army fort.
Include Color Illustrations
Keywords: History, Ancient